Reducing cultural barriers via Internet courses - Xing, Minjie; Spencer, Ken (Innovations in education and teaching international, 2008)
A Web-based learning environment has been developed to support students from China who are studying in the UK and are confronted by many cultural barriers, which may impede their academic studies. The electronic environment incorporates a number of approaches to support learning, ranging from a simple text-based presentation to more active methods, including opportunities to use search-based learning strategies. Experimental results demonstrate a clear advantage for these active approaches. Internet support was also provided for students in the form of an e-learning course for academic writing, which featured extensive opportunities for interactions with English peers. The experimental results demonstrated that the group with access to the e-course successfully acquired skills, resulting in their academic writing being indistinguishable from native English speakers.